Copyright Law awareness and compliance in selected university libraries in Metro Manila - Terante, David C. (School of Library and Information Studies, University of the Philippines Diliman, 2015)
This study aimed to determine the level of copyright law awareness if six librarians and ninety-eight section heads. unit head librarians and library staff in six selected university libraries in Metro Manila. It also aimed to determine whether the six selected university libraries comply with the copyright law. The information about the subjects' copyright awareness and compliance were obtained through a survey questionnaire with a checklist format. The questionnaire was demonstrated to a panel of faculty members for their remarks and proposals to integrate with the testing. The questionnaire also identified the following: 1. Library policies implemented to prevent copyright violation; 2. Copyright promotions being implemented in the libraries; 3. Copyright problems librarians encounter and possible solutions. Part of the questionnaire is a copyright law awareness test, wherein most found to be moderately aware (42.3%) on the copyright law. The rest were either highly aware (32.7%) or slightly aware (15.4%) on the copyright law. Majority (76.9%) of the libraries had policies related to copyright policies while forty-one (39.4%) respondents indicated they had verbal / oral copyright policies.